2017
DOI: 10.1101/gad.305888.117
|View full text |Cite
|
Sign up to set email alerts
|

The secreted neurotrophin Spätzle 3 promotes glial morphogenesis and supports neuronal survival and function

Abstract: Most glial functions depend on establishing intimate morphological relationships with neurons. Significant progress has been made in understanding neuron-glia signaling at synaptic and axonal contacts, but how glia support neuronal cell bodies is unclear. Here we explored the growth and functions of cortex glia (which associate almost exclusively with neuronal cell bodies) to understand glia-soma interactions. We show that cortex glia tile with one another and with astrocytes to establish unique central nervou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(137 citation statements)
references
References 62 publications
8
129
0
Order By: Relevance
“…Additional experiments indicated that ClC‐a + nuclei present on the surface of the CB and in cortical areas belonged to cortex glia. The membrane and nuclear patterns of ClC‐a + cells were consistent with the nuclear patterns and the membrane scaffold, also known as the trophospongium (Hoyle, Williams, & Phillips, ), observed with the recently described cortex glia driver wrapper (Coutinho‐Budd et al, ) (compare Figure g with Figure l). In fact, there was extensive colocalization between ClC‐a + and wrapper + membranes in the CB and OL (Figure m,n), including surface‐associated cortex glia on the OPC (Figure n,n'').…”
Section: Resultssupporting
confidence: 86%
“…Additional experiments indicated that ClC‐a + nuclei present on the surface of the CB and in cortical areas belonged to cortex glia. The membrane and nuclear patterns of ClC‐a + cells were consistent with the nuclear patterns and the membrane scaffold, also known as the trophospongium (Hoyle, Williams, & Phillips, ), observed with the recently described cortex glia driver wrapper (Coutinho‐Budd et al, ) (compare Figure g with Figure l). In fact, there was extensive colocalization between ClC‐a + and wrapper + membranes in the CB and OL (Figure m,n), including surface‐associated cortex glia on the OPC (Figure n,n'').…”
Section: Resultssupporting
confidence: 86%
“…Proliferation is likely to occur during larval stages, as determined by an increase in nuclear counts, and is in part regulated by FGF‐receptor Heartless (Htl) and Insulin receptor signaling but not via the PI3K/TOR pathway (Avet‐Rochex et al, ). During metamorphosis cortex glial cells remain and stay into adulthood (Coutinho‐Budd, Sheehan, & Freeman, ). In abdominal neuromeres of the ventral nerve cord of third instar larvae, single cortex glial cells engulf the entire lineage of a neural stem cell comprising on average 55 neurons (Coutinho‐Budd et al, ; Dumstrei, Wang, & Hartenstein, ; Pereanu et al, ; Spéder & Brand, ).…”
Section: Cortex Glial Cellsmentioning
confidence: 99%
“…As development proceeds, these glial cells extend processes around the stem cells as well as their progeny to establish non‐overlapping spatial domains. The growth of cortex glial cells is limited by astrocyte‐like glial cells encasing the neuropil (Coutinho‐Budd et al, ). Tiling and growth of cortex glial cells requires several components of the vesicle fusion and recycling machinery and the cell autonomous action of the secreted neurotrophin Spätzle 3 (Coutinho‐Budd et al, ).…”
Section: Cortex Glial Cellsmentioning
confidence: 99%
See 2 more Smart Citations